Research on the stability evaluation method of anchored slopes based on group decision making and matter element analysis - Peng Xia (Nature Portfolio, 2021)
Abstract This research is focused on the evaluation method of anchored slope stability, and an accurate evaluation method with a simple operation is proposed. Group decision theory and the analytic hierarchy process are used to determine the weight of each evaluation element, the correlation degree of each indicator is determined based on matter element analysis theory, and inverse hierarchical calculations are performed based on the obtained weight value and correlation degree to finally obtain the criteria layer correlation degree used for stability evaluation. The results show the following: (1) the evaluation method better integrates the effects of multiple factors on the stability of the anchored slope, and the evaluation results are accurate and consistent with the actual situation of the project; (2) the evaluation method can make full use of the experience of the expert group and effectively avoid the evaluation error caused by the subjective deviation of a single expert; (3) the group decision theory-entropy model was introduced to realize the quantitative evaluation of the reliability of expert scoring and effectively improve the efficiency of expert discussion; and (4) the evaluation result is intuitive, and the correlation degree obtained can not only reflect the stability grade of the anchored slope but also reflect the "distance" between the anchored slope and other stability grades.